Pollen Viability, Pistil Receptivity, and Embryo Development in Hybridization of Nelumbo nucifera Gaertn. (2nd May 2012) - Wang, Yan-Li; Guan, Zhi-Yong; Chen, Fa-Di; Fang, Wei-Min; Teng, Nian-Jun
Abstract : Seed set is usually low and differs for different crosses of flower lotus ( Nelumbo nucifera Gaertn.). The reasons remain unknown, and this has a negative impact on lotus breeding. To determine the causes, we carried out two crosses of flower lotus, that is, "Jinsenianhua" × "Qinhuaihuadeng" and "Qinhuaihuadeng" × "Jinsenianhua" and pollen viability, pistil receptivity, and embryo development were investigated. The pollen grains collected at 05:00-06:00 hrs had the highest viability, and the viabilities of "Jinsenianhua" and "Qinhuaihuadeng" were 20.6 and 15.7%, respectively. At 4 h after artificial pollination, the number of pollen grains germinating on each stigma reached a peak: 63.0 and 17.2 per stigma in "Jinsenianhua" × "Qinhuaihuadeng" and "Qinhuaihuadeng" × "Jinsenianhua", respectively. At 1 d after artificial pollination, the percentages of normal embryos in the two crosses were 55.0 and 21.9%, respectively; however, at 11 d after pollination, the corresponding percentages were 20.8 and 11.2%. Seed sets of the two crosses were 17.9 and 8.0%, respectively. The results suggested that low pistil receptivity and embryo abortion caused low seed set in "Qinhuaihuadeng" × "Jinsenianhua", whereas low fecundity of "Jinsenianhua" × "Qinhuaihuadeng" was mainly attributable to embryo abortion.